Fatores de forma do decaimento radiativo do píon usando o modelo Nambu-Jona-Lasinio - Arthur Cesar Dinali Viglioni (2013)
The radiative decays of the pion are comparatively rare, however, experiments nowadays are becoming more precise. The goal is to use such decays, which occur at relatively low energies (E < 2 Gev, typically), to test the Standard Model instead of using high energies. We calculate the Vector Form Factor (FV ) and the ratio between Axial-Vector (FA)and Vector Form Factors to the radiative decay ! ee and we compare with their experimental values. In this decay, the three interactions of Standard Model are present. Particularly, the strong interaction, in what is currently accepted that Quantum Chromodynamics(QCD) describes it. The problem is that, as previously stated, this kind of decay occurs at relatively low energies, so it's necessary to use the QCD in the non-perturbative regime, where the Feynman calculations become useless. An alternative to this is to use a simpler model and which incorporates part of the features of QCD. In this work, we use the Nambu-Jona-Lasinio Model, since it reproduces very well the features of QCD at low energies. We are able to describe FV , however not the ratio between FA and FV , which probably indicates that the other interactions should be included, as e.g. the p meson.